2017
DOI: 10.1088/1674-1056/26/1/015201
|View full text |Cite
|
Sign up to set email alerts
|

Fluid simulation of the pulsed bias effect on inductively coupled nitrogen discharges for low-voltage plasma immersion ion implantation

Abstract: Planar radio frequency inductively coupled plasmas (ICP) are employed for low-voltage ion implantation processes, with capacitive pulse biasing of the substrate for modulation of the ion energy. In this work, a two-dimensional (2D) selfconsistent fluid model has been employed to investigate the influence of the pulsed bias power on the nitrogen plasmas for various bias voltages and pulse frequencies. The results indicate that the plasma density as well as the inductive power density increase significantly when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The 2D fluid module, which has been described in earlier studies, [17][18][19][20] is mainly composed of a plasma module and an electromagnetic module.…”
Section: Fluid Modulementioning
confidence: 99%
See 1 more Smart Citation
“…The 2D fluid module, which has been described in earlier studies, [17][18][19][20] is mainly composed of a plasma module and an electromagnetic module.…”
Section: Fluid Modulementioning
confidence: 99%
“…Because the distribution of plasma characteristics is vital for controlling the process of semiconductor etching, it is of great interest to elucidate the effect of bias on the plasma distributions. Therefore, in this study, the multi-physics analysis for plasma sources-ICP (MAPS-ICP) solver [17][18][19][20][21] composed of a fluid module and a sheath module [22,23] is employed to investigate the effects of single-frequency and dual-frequency bias on the plasma characteristics at different values of ICP source power. Our results provide a useful insight into the effect of source power, which can be used for optimizing the plasma processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical model can aid in determining the optimal conditions for producing the ideal plasma. Sun et al [13,14] studied ICP plasma characteristics by using two-dimensional self-consistent fluid model. It was found that the spatial distribution of plasma characteristics was controlled by changing the bias power of single frequency bias or high frequency bias power ratio of double frequency offset.…”
Section: Introductionmentioning
confidence: 99%